KUALIFIKASI MANAJEMEN LEMBAGA KEUANGAN MENURUT PETUNJUK SYARIâAH - Jannah, Sofwan (Islamic University of Indonesia, 2003)
The syaria finance institution (LKS) can be managed well, if itâs done by professional people who have commitment to Islamic syaria, in order to get guidance of Allah SWT. Appreciation and society belief of syaria finance institutionâs activities in Indonesia today. Bank Muamalat Indonesia (BMI) who gets the 7th grade and 13th for Bank Syariah Mandiri (BSM) of 62 banks, have given the evidence of the management and work of syaria finance institution arnât worse then the convensional finace institution.